Dampak Literacy Keuangan terhadap Strategi Keberlanjutan Bisnis dalam UMKM - Hariyanti, Dini; Sekar Mayangsari; Vinola Herawaty; Rismayanti; Dewi Anggraeni (PT. Cendekia Sapta Indonesia, 2025)
This community service program was conducted by the Faculty of Economics and Business, Trisakti University, to improve financial literacy and business sustainability among MSMEs in Gudang Sarinah Pancoran, South Jakarta. Field observations revealed common issues, including the absence of separation between personal and business finances and weak budgeting practices. The program was implemented through training, workshops, consultations, and mentoring, with evaluation using pre- and post-tests. The results showed a 40% increase in participants’ financial literacy scores, 70% of participants began separating personal and business finances, and 50% reported revenue growth of 10–15% within three months. These findings highlight the direct impact of financial literacy interventions on MSME financial practices. Program sustainability was supported by continued mentoring sessions, ensuring consistent application of the acquired skills. Overall, the program demonstrates that strengthening financial literacy is a practical strategy to enhance MSME competitiveness and long-term sustainability.